A headache not to be sneezed at. Issue 5 (22nd April 2009) - Garry, D; Forrest-Hay, A
Abstract : A 32-year-old male patient presented to the emergency department (ED) complaining of a headache and vertigo precipitated by sneezing. He had a recent history of neck trauma. Examination revealed horizontal nystagmus and a gait that veered to the left, exacerbated by heel to toe walking. A diagnosis of vertebral artery dissection (VAD) was suspected. A bleed was ruled out in the ED by computerised tomography, after which the patient was loaded with aspirin. The diagnosis was confirmed by magnetic resonance imaging and magnetic resonance angiography. Although optimal treatment for VAD is unknown, the Cervical Artery Dissection in Stroke Study (CADISS) is an ongoing randomised multicentre prospective study comparing antiplatelet therapy with anticoagulation for patients with both carotid artery dissection and VAD. Headache is a very common presentation to the ED and a full neurological examination is essential if rarer causes are not to be missed.